Improved double-gate armchair silicene nanoribbon field-effect-transistor at large transport bandgap. (7th December 2015) - Mahmoudi, Mohsen; Ahangari, Zahra; Fathipour, Morteza
Abstract: The electrical characteristics of a double-gate armchair silicene nanoribbon field-effect-transistor (DG ASiNR FET) are thoroughly investigated by using a ballistic quantum transport model based on non-equilibrium Green's function (NEGF) approach self-consistently coupled with a three-dimensional (3D) Poisson equation. We evaluate the influence of variation in uniaxial tensile strain, ribbon temperature and oxide thickness on the on-off current ratio, subthreshold swing, transconductance and the delay time of a 12-nm-length ultranarrow ASiNR FET. A novel two-parameter strain magnitude and temperature-dependent model is presented for designing an optimized device possessing balanced amelioration of all the electrical parameters. We demonstrate that employing HfO2 as the gate insulator can be a favorable choice and simultaneous use of it with proper combination of temperature and strain magnitude can achieve better device performance. Furthermore, a general model power (GMP) is derived which explicitly provides the electron effective mass as a function of the bandgap of a hydrogen passivated ASiNR under strain.